Online student response systems and student engagement in large EFL classrooms (Journal of Applied Learning and Teaching, 2022)
This study investigated how the use of online student response systems (OSRS) in conjunction with an active question and answer technique affected student engagement and achievement in on-ground classes. Quantitative and qualitative data from 118 undergraduate nursing students, related to the change from classical to online question-answer (QA) activities, were collected using pretests, posttests, questionnaires and interviews. Two systems (Zuvio and Socrative) were introduced, allowing all students in large classroom environments to share their answers with personal smartphones before teacher feedback was given. The findings indicate that the question-answer activity using OSRS improves and retains student engagement in large classes. Two factors that contribute to the high engagement include anonymity and personalized feedback.